Geometry in Banyumulek Pottery Craft: Cultural Heritage and Mathematical Implementation - Dwi Sinta Aulya; Sri Santika; Ahmad Hamid (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Culture is a part of everyday life that can be used as a learning resource, including in mathematics education. This approach is known as ethnomathematics. Each region has its own unique cultural heritage, such as Banyumulek Village, which is known for its traditional pottery that has been passed down through generations. The purpose of this study is to identify the concepts of geometric mathematics found in the pottery craft of Banyumulek Village so that they can be used as learning resources in mathematics education. This research uses qualitative research with an ethnographic approach. Data collection was carried out through observation, interviews, documentation, and literature study. This research was conducted in Banyumulek Village, Kediri District, West Lombok, NTB. The results showed that in pottery (glass, ball, cobek, plate, jug, and momolo) there is a concept of mathematical geometry in some of the pottery, namely: curved surface solids, polyhedrons, and flat geometry. The concept of flat circular geometry is found on the plate, and cobek, while the tube shape is found in the glass. Ethnomathematics can help students understand everyday problems more easily.